The impact of COVID-19 on burnout among healthcare workers - literature review - Martyna Nowińska; Justyna Dziekońska; Paulina Grabowy; Martyna Drożak; Joanna Milanowska (Kazimierz Wielki University, 2021)
Introduction: The COVID-19 pandemic broke out in Wuhan, China, in December 2019. Coronavirus disease is commonly transmitted through contact transmission and direct contact. Considering the transmission mechanism of the virus, healthcare workers are at high risk of becoming infected. SARS-CoV-2 has became a major stressor for medical staff, that can lead to burnout. The aim of the study: Paying attention to the correlation between COVID-19 pandemic and burnout among healthcare workers. Material and method: The research was done by the usage of the PubMed and Google Scholar articles about the topic of: burnout; healthcare workers, COVID-19 pandemic, mental health, stress. Description of the state of knowledge: According to various studies, the COVID-19 pandemic may have negative impact on the mental health of healthcare workers. Worsening systemic stressors may lead to professional burnout. Latest research has identified associations between burnout and inadequate psychological support, direct contact with infected patients, and working in the nursing profession. Summary: The results from all studies proved that the COVID-19 pandemic has tremendous impact on professional burnout among medical staff. It is essential to pay attention to the psychological wellbeing of healthcare workers.